Importance of unpaired electrons in organic electronics. Issue 2 (11th August 2014) - Yuen, Jonathan D.; Wang, Mingfeng; Fan, Jian; Sheberla, Dennis; Kemei, Moureen; Banerji, Natalie; Scarongella, Mariateresa; Valouch, Sebastian; Pho, Toan; Kumar, Rajeev; Chesnut, Eneida C.; Bendikov, Michael; et al.
ABSTRACT The first observation that PBBTPD, a low bandgap, ambipolar conjugated donor‐acceptor (DA) polymer based on benzobisthiadiazole (BBT), possesses an open‐shell singlet ground state as well as a thermally accessible triplet state is described. Similarly, interesting electronic behavior in semiconducting organic DA oligomers based on BBT is also observed. Theoretical predictions have suggested that such behavior is due to the biradicaloid character of BBT and we provide experimental evidence indicating that these predictions are correct. Furthermore, the open shell character strengthens as the conjugation length increases, as observed in the BBT‐based polymer, PBBTPD. We show that this biradicaloid structure is observed in each BBT moiety along the chain and that therefore PBBTPD is in fact a polyradicaloid. This observation will most likely aid in the development of better n‐type polymeric acceptors for organic semiconductor applications. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 287–293